Characterization study on machining PMMA thin‐film using AFM tip‐based dynamic plowing lithography. Issue 6 (18th February 2016) - Yan, Yongda; He, Yang; Geng, Yanquan; Hu, Zhenjiang; Zhao, Xuesen
Summary: This paper presents a reliable nanolithography technique, namely dynamic plowing lithography (DPL) based on a commercial atomic force microscope (AFM). The poly(methyl methacrylate) (PMMA) solution spinning on a silicon substrate is utilized to be scratched directly with an oscillating tip at its resonance frequency. The films with different thickness are obtained by adjusting the concentration of solution and post baked time. A new silicon tip is employed to conduct DPL on PMMA film surface. The geometry of nano‐line structure scratched on the film with high adhesion force is shown with a transition process, including total protuberance, protuberance with groove and groove with pile‐up. The scratching direction has less influence on the scratched depth of groove, while the shape of pile‐up is varied with directions. The depth of groove on thin films is increasing with the drive amplitude until the value of the depth reaches to the threshold value. Moreover, owing to smaller elastic modulus, the film with relatively large thickness could be modified by the tip more easily using this DPL method. SCANNING 38:612–618, 2016. © 2016 Wiley Periodicals, Inc.